EVALUATION OF MODERN RITEL POLICY INTEMBALANG SEMARANG CITY - Fitriana, Ciciek; Purnaweni, Hartuti; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2014)
Modern market such as minimarket and modern shop are now growing fast in Tembalang regency, Semarang. This condition would probably give negative effects so evaluation of retail policy is needed in that area. The purpose of this research are to examine the impact of modern retail policy and to know the possible effort the can be conducted to reduce the modern retail effect in Tembalang regency. Qualitative methodology is used to describe the phenomena as the focus of the research. The source persons of this research are Semarang government officials, traditional merchants, and the society surround Tembalang regency. The result of the research shows the development of modern market namely minimarket and modern shop in Tembalang regency is growing rapidly year by year. According to Trade and Industry Department of Semarang, in 2012 there were 39 modern shops in Tembalang regency. That data was considered incomplete considering to the fact since numbers of modern shops in several spots beside the street was not included within the list. The appearance of modern shop creates positive and negative effects. The positive effect, it can increase the PAD of Semarang as a city and ease the consumer. The negative effects are it can also depress traditional merchants profit and create resistance as well as social gap. The suggestion of this research is hopefully, the government of Semarang would improve traditional market as new public service paradigm which upholds public importance along with the conduct of supervision in order to reduce the effect of the policy.